2017
DOI: 10.2139/ssrn.3086671
|View full text |Cite
|
Sign up to set email alerts
|

Motivating Whistleblowers

Abstract: Law-breaking activities within an organization bene…ting the …rm at the expense of the general public are widespread but di¢cult to uncover, making whistleblowing by employees desirable. We employ a novel laboratory experiment to investigate if and how monetary incentives and expectations of social approval or disapproval, and their interactions, a¤ect the decision to blow the whistle. Experimental results show that: i) …nancial rewards signi…cantly increase the likelihood of whistleblowing and do not substant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Based on the explanation from the Prosocial Behavior Theory, providing financial rewards to whistleblowers is expected to encourage whistleblowing intentions. Previous researches on the effect of financial reward on whistleblowing intentions indicated that financial reward influenced whistleblowing intentions; or in other words, given financial rewards would encourage whistleblowing intentions (Andon et al, 2016;Schmolke & Utikal,2016;Butler et al, 2017;and Xu & Ziegenfuss, 2008). Based on this explanation, the hypothesis is: H1: Whistleblowing will be greater, if given a financial reward compared to not given a financial reward.…”
Section: Financial Reward and Whistleblowing Intentionmentioning
confidence: 96%
“…Based on the explanation from the Prosocial Behavior Theory, providing financial rewards to whistleblowers is expected to encourage whistleblowing intentions. Previous researches on the effect of financial reward on whistleblowing intentions indicated that financial reward influenced whistleblowing intentions; or in other words, given financial rewards would encourage whistleblowing intentions (Andon et al, 2016;Schmolke & Utikal,2016;Butler et al, 2017;and Xu & Ziegenfuss, 2008). Based on this explanation, the hypothesis is: H1: Whistleblowing will be greater, if given a financial reward compared to not given a financial reward.…”
Section: Financial Reward and Whistleblowing Intentionmentioning
confidence: 96%
“…Schmolke and Utikal ( 2016) study the frequency of whistleblowing generated by rewards, fines for not blowing the whistle, as well as whether, and how, the enforcing authority is affected by the whistleblower's report. Butler et al (2017) study the interaction between monetary rewards, the visibility of the crime reported, and public image concerns of the whistleblowers. Most relevant for us, both studies find that, controlling for other factors, monetary rewards are very effective in increasing the probability of whistleblowing.…”
Section: Related Literaturementioning
confidence: 99%